Reading assessment system on online (RASO) - Nor Sazana, Moh Sahaimi (2012)
The purpose of this project is to develop Reading Assessment System on Online.It is a system that helps teachers and students in the management of reading assessment activity. Reading Assessment activity is an annual activity in the school.The reason to develop the system is due to the issues facing in managing the reading assessment activity.The issues are such teachers need to wait their students submit their book report of reading assessment to them before they can give the report of student’s reading assessment to the management, students need to buy the reading assessment book to write their reading assessment,the students also need to find their teacher to submit and show their reading assessment report’s book and the organizer of this reading assessment activity facing problem in collecting all the report from each teachers to know whose students have the highest of book reader.Therefore,this system to help teachers minimize task in updating their student’s reading assessment report.Besides that,it help teacher in monitoring student reading activity.Furthermore,this system provides a user-friendly web pages and effective data storage to the teachers and students with the advantage of Information and Communication Technology (ICT) in school.The structured methodologies have been chosen to develop the Reading Assessment System on Online. Rapid Application Development (RAD) encouraged the creation of quick and higher of quality through gathering requirements using workshops.The methodology used involved requirements Planning, user design, construction and cutover.